UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KREATIFITAS GURU DI MI MUHAMMADIYAH 15 BANJARWATI PACIRAN LAMONGAN - M. CHOTIBUDDIN (Jurnal Pendidikan Islam, 2019)
Abstract : The aim of this research is to analyze the efforts of Principal in improving the creativity of teachers in MI Muhammadiyah Lamongan 15 Banjarwati Paciran which was held in October 2016 and November 2016. This research uses descriptive research to obtain data from observation, interview and documentation. The research sample are principals and all teachers in 15 Banjarwati Paciran MI Muhammadiyah Lamongan. The Efforts that can be made by the principal in improving the creativity of teachers are 1) giving reward for creative teachers. 2) giving the career path 3) giving training systems